Ayurvedic Management of Hydrosalpinx: A Case Report (AYUSHDHARA, 2022)
Infertility is caused by different factors like ovulatory, endometrial, tubal factors etc., and tubal factors are more responsible for infertility in patients of chronic pelvic inflammatory disease. Among the Garbha Sambhava Samagri, tubal factors come under Kshetra Vikriti. The present article a case report of female with primary infertility with the involvement of bilateral hydrosalpinx is presented. A female patient aged about 27 years approached the OPD of Prasutitanntra and Striroga department, Arogyashala of National Institute of Ayurveda, Jaipur. Her initial complaints were severe pain before the onset of menstruation, intermittent on and off pain in left inguinal region, scanty menstruation and primary infertility. She was found to have huge hydrosalpinx in her USG findings. So treatment was planned accordingly and she was treated with Ayurvedic regimen consisting of Shodhana and Shamana therapy. Yonivarti was planned as Sthanika chikitsa along with Triphala Guggulu and Godanti bhasma as oral medications. Her USG was repeated after treatment which revealed hydrosalpinx was resolved possessing normal fallopian tube diameter.